A qualitative exploration of owner experiences following dog adoption - Bethany Joy Moyer; Helen Zulch; Beth Ann Ventura; Oliver Burman (Animal Welfare)
The adjustment period — wherein adopted animals transition to their new home — is a critical time for animal welfare and owner satisfaction, yet literature varies in estimates of how long this period lasts in dogs. This study sought to better characterise the adjustment period in relation to owner experience and canine welfare and clarify its duration as perceived by owners. We used a qualitative approach to examine owner perceptions of duration and their experience of the adjustment period. Twenty-seven interviews were conducted and analysed using thematic content analysis. Six themes were described: adjustment period duration; behavioural indicators during adjustment; behaviours indicative of adjustment; factors influencing adjustment; owner change in routine; and adjustment concerns. Over half of participants perceived the adjustment period to last longer than four months. Behaviours used by owners to assess dog adjustment included: moderation of behavioural extremes (e.g. lethargy and restlessness); play; tail wagging; greeting; and learning their routine. Owners reported that prior experiences and medical needs impacted the adjustment duration, that they adjusted aspects of their lifestyle, and raised concerns about being the right fit for their dog. Future research should incorporate a longer time-frame to better understand how and when dogs adjust to a home, and as there is variation in dog behaviour during adjustment, it must also account for individual differences. As we develop a better understanding of how to characterise this period, adopters can be better prepared for the initial months of dog ownership, and interventions can be individualised to improve owner experience and dog welfare.